1970
DOI: 10.1017/s0079497x00013177
|View full text |Cite
|
Sign up to set email alerts
|

Cheshire Cat and Mickey Mouse: analysis, interpretation and the art of the La Tène Iron Age

Abstract: Nearly seventy years ago Wilhelm Worringer first wrote that ‘ultimately all our definitions of art are definitions of classical art’ (Worringer, 1953, 132). Today, the study of Western European art history, old or modern, the products of peasant craft-centres or urban ‘schools’, has in the course of time developed its own methodology and, almost, mystique. In contrast, the study of many branches of prehistoric art in Europe and elsewhere is all too often seen as a mere extension of the skilled but subjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…More distant descendants of this latter style can be found, however, in Britain. Perhaps the most obvious examples are the spouts from Leg Piekarski in Poland (a boar, from its crest), in our view indisputably a British export (Megaw 1963;Megaw 1970a dolphins, each with a bird's head at its tail end, and possibly part of an oil-lamp hanger. Their publisher, following Mansel Spratling, considers them to be Romano-British in origin, though they were discovered in the River Weser at Dorverden, Kr.…”
Section: Stylistic Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…More distant descendants of this latter style can be found, however, in Britain. Perhaps the most obvious examples are the spouts from Leg Piekarski in Poland (a boar, from its crest), in our view indisputably a British export (Megaw 1963;Megaw 1970a dolphins, each with a bird's head at its tail end, and possibly part of an oil-lamp hanger. Their publisher, following Mansel Spratling, considers them to be Romano-British in origin, though they were discovered in the River Weser at Dorverden, Kr.…”
Section: Stylistic Discussionmentioning
confidence: 93%
“…Horses are most commonly to be seen on coins rather than in three dimensions. In Britain, the fantastic creatures found on the European continent in early La Tene I on brooches and flagons, or in the third-century Disney style (Megaw 1970b) of (frequently reversible) animal figures, are not known. More distant descendants of this latter style can be found, however, in Britain.…”
Section: Stylistic Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Jacobsthal , 161–3) have also seen art historical analyses (overview in Garrow and Gosden , 44–56; cf. Olivier ; Megaw , 261–2, 276). Such studies also identified the limits of modern interpretation (Joy , 44; Müller ).…”
Section: Design Theory and Early Celtic Artmentioning
confidence: 99%